ANALYSIS OF STUDENTS TURN-TAKING IN GROUP WORK DISCUSSION - Flora, Flora; Emzir, Emzir (PPs UNJ, 2015)
This content analysis that belongs to qualitative research aims at finding indebth understanding about turn-takingÂ produced by S1 students of FKIP- Lampung University during group work discussion. The data were students utterances during group work discussion. All the data were recorded, transcribed, and were analyzed based on the context in order to find out the studentsâ turn-taking. The result shows that students made turn-taking during the group work discussion and it can be classified into two catagories, namely: 1) by choosing himself, and 2) by choosing others. The speaker chose himself by having four reasons while the speaker chose others by having three reasons. All the turn-takings are made by students in order to finish the task given by the lecturer.